Comparative analysis of pediatric rheumatic patient growth patterns against norms: A cross-sectional study conducted in an Eastern Indian hospital - Kausik Sur; Suparna Guha; Debabrata Manna; Ajitesh Roy; Tabasume Khatun (Romanian Journal of Rheumatology)
Background. Juvenile idiopathic arthritis (JIA) is the most common rheumatic disease. Rheumatic diseases are a major cause of chronic illness in children around the world. SLE is a further prevalent inflammatory illness. Aims and objectives. To study different growth parameters of Pediatric patients attending Pediatric Rheumatology clinic, to compare the growth parameters with age and sex matched Controls and to compare growth among different types of Pediatric rheumatic patients. Method. Different growth parameters and SMI (for children above 9 years) were recorded for patients attending Pediatric Rheumatology OPD having disease duration more than one year. Results. Among 121 patients, JIA was most common followed by SLE. Among JIA subtypes, SOJIA is most common. Mean age of presentation was earlier in SOJIA, late in JoAS. SLE patients had larger Duration of illness prior to diagnosis than JIA patients. In JIA patients, mean height was significantly less than controls. SOJIA and Polyarticular variety had significantly less weight and height compared to controls. SLE patients had significantly less weight and height compared to control. Anthropometric Parameters were significantly more in SLE patients compared to JIA cohort. There was significantly more delayed puberty both in JIA and SLE patients compared to controls. Conclusion. JIA was most common, followed by SLE. Among JIA patients SOJIA variety was most common, JIA patients had significantly lower height than Controls. SLE patients had significantly lower weight and height than Controls. Delayed Puberty was significantly more in both JIA and SLE patients compared to controls.